Dualistic MADS-box evolution forged legume diversity post-WGD - Nan, Haiyang; Chen, Xinxin; Zhang, Jiajia; Zou, Mingyang; Shang, Erxuan; Guo, Xinyi; Kou, Kun (Frontiers in Plant Science, 2026)
The MADS-box gene family plays a central role in plant development and adaptation, yet its evolutionary history in legumes is remarkably complex. In this study, we performed a pangenomic analysis across 52 legume species, identifying 4,872 MADS-box genes and reconstructing their phylogeny into 16 subfamilies. Our analysis uncovered a pervasive dualistic evolutionary model driven by distinct duplication mechanisms. Structurally, the genes fall into two categories: the compact, intron-poor Type I and the complex, intron-rich Type II. We demonstrate that whole-genome duplication (WGD) serves as the major driver (42.2%) behind the expansion of the conserved core genome, which includes key floral regulators such as the “ABCDE model” genes. These WGD-derived genes are under strong purifying selection, thereby ensuring developmental stability. In contrast, small-scale duplication (SSD) fuels the expansion of the dynamic periphery, primarily composed of Type I genes and stress-responsive clades, which evolve under relaxed selection and promote lineage-specific innovation—as strikingly exemplified by the massive tandem expansion of the SVP subfamily in Prosopis. Pangenome analysis confirmed that WGD-derived genes were enriched in the conserved core genome, underpinning essential functions, whereas SSD-derived genes dominated the variable genome and acted as a source of genetic novelty. Transcriptome analysis in soybean identified four organ-specific expression modules, predominantly comprising Type II core genes. Under biotic and abiotic stress, WGD-derived gene pairs exhibited prominent asymmetric expression. The expression divergence was validated by qRT-PCR. Overall, our findings establish a unified framework for MADS-box gene evolution in legumes, illustrating how divergent duplication mechanisms and selective pressures have collectively shaped a gene family critical to both evolutionary innovation and developmental stability.